TEACHERS' STRATEGIES IN TEACHING LISTENING COMPREHENSION AT SENIOR HIGH SCHOOLS IN KARAWANG: A CASE STUDY - Amanda, Amelia; Kodir Al- Baekni, Abdul; Fitriyana, Wahyudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the strategies used by an English teacher in teaching listening comprehension at a high school in Karawang. This study employs a qualitative approach using a case study design. The research participant was an English teacher selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using the qualitative data analysis model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and drawing conclusions. The findings indicate that the teacher employed a combination of top-down and bottom-up strategies in teaching listening comprehension. Additionally, the teacher implemented listening instruction through three stages: pre-listening, during listening, and post-listening. These strategies effectively helped students understand the material by activating prior knowledge, focusing on linguistic features, and engaging them in structured listening activities. This study concludes that the integration of various listening strategies and systematic teaching stages contributes positively to the effectiveness of oral comprehension instruction in EFL classrooms and supports the development of students’ listening skills.